2005
DOI: 10.1038/sj.bjc.6602447
|View full text |Cite
|
Sign up to set email alerts
|

Identification of genes associated with platinum drug sensitivity and resistance in human ovarian cancer cells

Abstract: Platinum-based chemotherapeutic regimens are ultimately unsuccessful due to intrinsic or acquired drug resistance. Understanding the molecular basis for platinum drug sensitivity/resistance is necessary for the development of new drugs and therapeutic regimens. In an effort to identify such determinants, we evaluated the expression of approximately 4000 genes using cDNA microarray screening in a panel of 14 unrelated human ovarian cancer cell lines derived from patients who were either untreated or treated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
112
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(117 citation statements)
references
References 28 publications
5
112
0
Order By: Relevance
“…Although activation of STATl in some cell systems has been shown to be proapoptotic (Calo et al, 2003), a recent observation has indicated a role for STATl in mediating radiation resistance (Khodarev et al, 2004). Recently, a correlation between STATl expression and cisplatin resistance in cell lines derived from patients with ovarian carcinoma was also reported (Roberts et al, 2005), and inhibitors of the STATl pathway have been shown to induce apoptosis in leukaemic cells from patients (Martinez-Lostao et al, 2005). The pathway analysis showed that STATl is positively influenced by MAPK1 and FAK, two of the most highly connected resistance-associated genes, both of which have been reported to inhibit apoptosis (Shimada et al, 2002;Kurenova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although activation of STATl in some cell systems has been shown to be proapoptotic (Calo et al, 2003), a recent observation has indicated a role for STATl in mediating radiation resistance (Khodarev et al, 2004). Recently, a correlation between STATl expression and cisplatin resistance in cell lines derived from patients with ovarian carcinoma was also reported (Roberts et al, 2005), and inhibitors of the STATl pathway have been shown to induce apoptosis in leukaemic cells from patients (Martinez-Lostao et al, 2005). The pathway analysis showed that STATl is positively influenced by MAPK1 and FAK, two of the most highly connected resistance-associated genes, both of which have been reported to inhibit apoptosis (Shimada et al, 2002;Kurenova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Although Stat1-deficient mice do not display a heightened incidence of spontaneous neoplasms, they are more sensitive to chemical induction of tumors (Kaplan et al, 1998;Levy and Gilliland, 2000). However, STAT1 expression is frequently upregulated in tumors (Frank et al, 1997;Spiekermann et al, 2001;Widschwendter et al, 2002;Benekli et al, 2003;Hudelist et al, 2005) and associated with prosurvival functions under conditions of growth stress, such as X-irradiation (Khodarev et al, 2004), or anticancer therapy (Friedberg et al, 2004;Roberts et al, 2005). Even ectopic expression of IFNg can support tumor development via STAT1 activation (Wang et al, 2000;Lin et al, 2004).…”
Section: Stat1 Is a Prosurvival Factor In Wilms' Tumormentioning
confidence: 99%
“…Aside from the role of Stat1 in cisplatin resistance, micro-array analysis of an ovarian cancer cell line reveals an inverse relationship between increased Stat1 expression and drug sensitivity. Transfection of full-length Stat1 into drug-sensitive cancer cells has led to cisplatin resistance (16). However, the associated mechanisms remain unexplored.…”
Section: Discussionmentioning
confidence: 99%
“…The clinico-pathologic characteristics of Patients A and B were listed in Table 1 Different Patterns of Stat1 Activation in Cancer Cells from MPE had Different Sensitivities to Cisplatin Cisplatin was the main agent for treating advanced lung cancer (10). Because Stat1 activation might contribute to drug resistance of cancer cells (16,17), the relationship between Stat1 activation after IFN-c stimulation and cell sensitivity to cisplatin in cancer cells from MPEs was investigated. Cancer cells from MPEs of another six lung cancer patients were analyzed (Table 1, Patients 1-6).…”
Section: Scpfc and Western Blot Analysis Of Ifn-c-induced Stat1 Phospmentioning
confidence: 99%